Derivative Media: How Wall Street Devours Culture - Andrew deWaard (University of California Press, 2024)
Sequels, reboots, franchises, and songs that remake old songs—does it feel like everything new in popular culture is just derivative of something old? Contrary to popular belief, the reason is not audiences or marketing, but Wall Street. In this book, Andrew deWaard shows how the financial sector is dismantling the creative capacity of cultural industries by upwardly redistributing wealth, consolidating corporate media, harming creative labor, and restricting our collective media culture. Moreover, financialization is transforming the very character of our mediascapes for branded transactions. Our media are increasingly shaped by the profit-extraction techniques of hedge funds, asset managers, venture capitalists, private equity firms, and derivatives traders. Illustrated with examples drawn from popular culture, Derivative Media offers readers the critical financial literacy necessary to understand the destructive financialization of film, television, and popular music—and provides a plan to reverse this dire threat to culture. "The thoughtful and thought-provoking chapters of Derivative Media feel like cave paintings that future generations will read long after we've perished in the flames of greed. A must-read for anyone working in the arts wanting to help humanity change course quickly!" — Martin Starr, actor, Freaks and Geeks and Silicon Valley "The go-to account of our contemporary financialized culture. It will reshape media studies and give activists new tools to understand the dynamics of the now." — J. D. Connor, author, Hollywood Math and Aftermath: The Economic Image and the Digital Recession "This tour-de-force breakdown of financialization in the culture industries is essential reading for scholars and creative workers alike." — Jennifer Holt, author, Empires of Entertainment: Media Industries and the Politics of Deregulation, 1980–1996 "A generational advance in the political economy of communication. I have been waiting for a book like this." — Jonathan Sterne, author, MP3: The Meaning of a Format
Keywords: 330; Mass media; economic aspects; financialization; United States